2001
DOI: 10.1029/2000wr900316
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of aperture distribution, capillary pressure, relative permeability, and in situ saturation in a rock fracture using computed tomography scanning

Abstract: Abstract. We develop an experimental technique that uses computed tomography (CT)scanning to provide high-resolution measurements of aperture distribution and in situ saturation along with capillary pressure and relative permeability for the same roughwalled fracture. We apply this technique to an induced fracture in a cylindrical basalt core undergoing water drainage. We find that the sum of the water and gas relative permeabilities is much <1 at intermediate saturations and the water relative permeability sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 27 publications
3
94
0
2
Order By: Relevance
“…Dispersion of X-ray attenuation and partial volume effects can cause an expansion of the anomaly over adjacent voxels that gather this "missing attenuation" (Johns et al, 1993) and, in particular for larger fractures, represent a large portion of the entire anomaly. According to that, Johns et al (1993) suggested a calibration-based linear relationship between aperture width and the integral of the full measured anomaly which was subsequently confirmed in several fracture aperture studies (Bertels et al, 2001;Heriawan and Koike, 2015;Huo and Benson, 2015;Keller, 1997;Van Geet and Swennen, 2001;Vandersteen et al, 2003;Weerakone and Wong, 2010) and physically established by Huo et al (2016). Accordingly, the linearity between missing attenuation (CT MA ) and fracture aperture a can be simply described as…”
Section: Image Processingmentioning
confidence: 99%
“…Dispersion of X-ray attenuation and partial volume effects can cause an expansion of the anomaly over adjacent voxels that gather this "missing attenuation" (Johns et al, 1993) and, in particular for larger fractures, represent a large portion of the entire anomaly. According to that, Johns et al (1993) suggested a calibration-based linear relationship between aperture width and the integral of the full measured anomaly which was subsequently confirmed in several fracture aperture studies (Bertels et al, 2001;Heriawan and Koike, 2015;Huo and Benson, 2015;Keller, 1997;Van Geet and Swennen, 2001;Vandersteen et al, 2003;Weerakone and Wong, 2010) and physically established by Huo et al (2016). Accordingly, the linearity between missing attenuation (CT MA ) and fracture aperture a can be simply described as…”
Section: Image Processingmentioning
confidence: 99%
“…For measurement of the aperture of fractures, X-ray computed tomography (CT) as a nondestructive method was often used (Johns et al 1993;Keller 1997;Bertels et al 2001;Zhuang et al 2016a). This method can help to analyze geometric properties of induced fractures as well as fracture propagation (Renard et al 2009;Jia et al 2013;Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced experimental techniques have been used to characterize the void geometry of single fractures. The aperture distributions were often found to follow lognormal distributions approximately in most cases excluding some contact points [9,27]. Therefore, the apertures of the fracture were treated as lognormally distributed in this research.…”
Section: Single Fracture Modelmentioning
confidence: 99%